Bentuk Pelayanan Sosial Pada Panti Sosial Anak Remaja Nusa Putera Dalam Mengembalikan Keberfungsian Sosial Anak - Nur Syafni; Mujahiddin Mujahiddin (Jurnal Intervensi Sosial dan Pembangunan, 2021)
This research has a purpose to find out how the form of social services at the Nusa Putera Children's Social Home in restoring the social functioning of children at the Tanjung Morawa Youth Social Service UPT, North Sumatra. Social services provided to foster children are job skills training and social guidance. The purpose of this activity is so that the assisted children can live independently and are no longer out of school and to help the family economy. This research was conducted using a descriptive qualitative research method approach. The resource persons for this research were 17 people. The focus of this research is to see how the program planning process, program implementation process and children's social functioning. All service processes at UPT PSAR Tanjung Morawa are based on social work methods and basic science concepts of Out-of-school Education and community empowerment.Keywords: Social Services, Children's Social Institutions, Children's Social Functions.